Overview of systematic reviews of the effectiveness of reminders in improving healthcare professional behavior - Cheung, Amy; Weir, Michelle; Mayhew, Alain; Kozloff, Nicole; Brown, Kaitlyn; Grimshaw, Jeremy (Université d'Ottawa | University of Ottawa, 2012)
Abstract Objective The purpose of this project was to conduct an overview of existing systematic reviews to evaluate the effectiveness of reminders in changing professional behavior in clinical settings. Materials and methods Relevant systematic reviews of reminder interventions were identified through searches in MEDLINE, EMBASE, DARE and the Cochrane Library in conjunction with a larger project examining professional behavioral change interventions. Reviews were appraised using AMSTAR, a validated tool for assessing the quality of systematic reviews. As most reviews only reported vote counting, conclusions about effectiveness for each review were based on a count of positive studies. If available, we also report effect sizes. Conclusions were based on the findings from higher quality and current systematic reviews. Results Thirty-five reviews were eligible for inclusion in this overview. Ten reviews examined the effectiveness of reminders generally, 5 reviews focused on specific health care settings, 14 reviews concentrated on specific behaviors and 6 reviews addressed specific patient populations. The quality of the reviews was variable (median = 3, range = 1 to 8). Seven reviews had AMSTAR scores >5 and were considered in detail. Five of these seven reviews demonstrated positive effects of reminders in changing provider behavior. Few reviews used quantitative pooling methods; in one high quality and current review, the overall observed effects were moderate with an absolute median improvement in performance of 4.2% (IQR: 0.5% to 6.6%). Discussion The results support that modest improvements can occur with the use of reminders. The effect size is consistent with other interventions that have been used to improve professional behavior. Conclusion Reminders appear effective in improving different clinical behaviors across a range of settings.